Pengaruh Edukasi Keluarga terhadap Kemampuan Keluarga dalam Merawat Klien dengan Isolasi Sosial - Muhammad Amin; Yoga Saputra; Deoni Vioneery (Journal of Telenursing (JOTING), 2019)
The purpose of this research is to know what happened in RSKJ Soeprapto Bengkulu, which is domiciled in Bengkulu City. This research is a quantitative research. The type of this research approach is quasi experimental research with One-Group Pre-test and post test design. The sample in this study were 15 patients who underwent outpatient at RSKJ Soeprapto Bengkulu which is domiciled in Bengkulu City, the sample was taken by purposive sampling technique. The results of this study indicate the influence of family education on family ability in treating patients with social isolation disorder in RSKJS Bengkulu Province with P = 0,000 (<0,05). Based on the results of this study, can be used as information for families in caring for patients who treat social disorders at the time of the family visited the Hospital. Keywords: Family Education, Family’s Ability, Social Isolation